Evaluation of mechanisms for trans-nationalizing research and development for reducing life cycle - F. A. Kurakov (Ekonomika Nauki)
The article demonstrates that alongside the process of trans-nationalizing the scientific driven and hightech production there is a trend arising in trans-nationalising scientific-technological sphere and global venture capital. There is evaluated the scale of the diffusion of Russian venture capital and its investment preferences. Using the examples of projects, related to the development of the new generation of antitumor drugs, there are analysed models for reducing the life cycle of domestic scientific developments in the format of using the benefits of various national innovation ecosystems and practices. A conclusion is made about the relevancy of reproduction of the life cycle of a high-tech product in the global scope of resources, markets and investments.